Microsurgical treatment of cranial and spinal dural arteriovenous fistulas for acute occlusion: a single institution's experience - Winter, F.; Böhm, Lea; Shawarba, Julia; Callegari, K.; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2022)
Objectives: To determine the success rate of primary microsurgical treatment of both cranial and spinal dural arteriovenous fistulas (cdAVFs and sdAVFs).
CRIS-Team WoS Importer:2022-08-26